Outcome at 8 years for children with birth weights of 1250 g or less. Issue 3 (March 1993) - Marlow, N; Roberts, L; Cooke, R
Abstract : The educational, motor, and behavioural performance of a hospital based cohort of 51 children aged 8 years with birth weights of 1250 g or less is reported, as part of a longitudinal study. Compared with age, race and sex matched classmates, who were examined at school at the same visit, the very low birthweight (VLBW) group performed less well on the basic mathematics test A, the Schonell spelling test, and the test of motor impairment. Reading performance was also poorer in this group. Twenty three (45%) VLBW children were having difficulty with one or more school subjects compared with 11 (19%) controls, and 15 (26%) had difficulties in two or more areas, compared with three (5%) controls. Parents of VLBW children reported a similar frequency of behavioural problems to controls but teachers identified characteristics typical of emotional disorders and overactivity more frequently among the VLBW group. Motor testing at 6 years of age was the best predictor of school problems at 8 years, correctly identifying 15/16 children with multiple problems with a low (33%) positive predictive value but a high (98%) negative predictive value. Children with birth weights of 1250 g or less and no major impairment have a high frequency of learning difficulties that become more apparent with advancing age. Such problems may be predicted at an earlier age by detailed motor testing.